Active ingredients of traditional Chinese medicine for enhancing the effect of tumor immunotherapy - Yang, Chao; Li, Dan; Ko, Chung-Nga; Wang, Kai; Wang, Haiyong (Frontiers in Immunology, 2023)
Immunotherapy has become the most promising method in cancer treatment. Studies have shown that traditional Chinese medicine (TCM) has antitumor activity and can also enhance host immunity. This article briefly describes the immunomodulatory and escape mechanisms in tumors, as well as highlights and summarizes the antitumor immunomodulatory activities of the active ingredients of TCM. Finally, this article puts forward some opinions on the future research and clinical application of TCM, aiming to promote the clinical applications of TCM in tumor immunotherapy and to provide new ideas for tumor immunotherapy.